Addressing Challenges To Strategic Management Adoption In Indian Msmes (Journal of Namibian Studies : History Politics Culture, 2023)
The implementation of strategic management methods in Indian Micro, Small, and Medium Enterprises (MSMEs) is met with a multitude of problems. These challenges range from structural restrictions and cultural opposition to regulatory impediments and technical slowness. Both the design and implementation of strategic plans are hampered by the inherent resource limits, which, when combined with the conventional hierarchical culture of the organization, contribute to the difficulties. The process of adoption is made much more difficult by cultural issues, such as a lack of understanding and an aversion to change. The performance of micro, small, and medium-sized enterprises (MSMEs) may be improved through strategic management, according to significant study. However, the majority of Indian micro, small, and medium-sized enterprises (MSMEs) do not adopt strategic management, and the reasons for this lack of strategic management in Indian MSMEs are not well understood. In this article, the conventional method of comprehending the significance of strategic management is called into question, and a set of guidelines for implementing strategic management in order to steer businesses away from failure is presented.